Advances in interleukin-10-based therapies for pulmonary diseases: focus on targeted lung delivery systems - Tian, Weikun; Wang, Xu; Zeng, Jia; Gao, Ya; Tang, Shuo; Ma, Caifeng; Ye, Liping; Tian, Xinghan (Frontiers in Immunology, 2025)
Interleukin-10 (IL-10) is an anti-inflammatory cytokine that exerts diverse effects on immune regulation. It alleviates excessive inflammatory responses in the body by inhibiting the expression of pro-inflammatory cytokines and the activation of antigen-presenting cells. In recent years, the therapeutic potential of IL-10 in various pulmonary inflammatory diseases has attracted extensive attention, including acute lung injury (ALI), acute respiratory distress syndrome (ARDS), asthma, and pulmonary fibrosis. IL-10 has also been studied in lung transplantation to improve the pro-inflammatory cytokine profile of donor lungs that do not meet conventional criteria. Nonetheless, its limited bioavailability, short half-life and potential for systemic adverse effects constrain its clinical application. To enhance its therapeutic efficacy and lung tissue targeting, intranasal administration and nebulized inhalation are the earliest methods applied in pulmonary diseases. Recombinant proteins, engineered mesenchymal stem cells, nanoparticle delivery systems, and gel delivery systems have also been developed and are undergoing preclinical trials. Many drug delivery platforms and pulmonary-targeted approaches have been shown to effectively increase the drug’s accumulation in the lungs and sustain its release, thus minimizing systemic toxicity. These IL-10-based therapies for pulmonary diseases can be broadly categorized into two main strategies: prolonging the half-life of exogenous IL-10 and enhancing the secretion of endogenous IL-10. The former mainly includes the development of IL-10 fusion proteins, nanoparticle delivery systems, and hydrogel delivery systems. The latter primarily involves IL-10 expression plasmids and IL-10-expressing adenoviruses. Despite its therapeutic potential, the clinical translation of IL-10 remains challenging. Its narrow therapeutic window constrains efficacy, and factors such as patient heterogeneity, disease stage, and the dynamic regulation of IL-10 signaling complicate the establishment of optimal dosing regimens. Emerging targeted delivery strategies provide opportunities to overcome these limitations by enabling precise spatial and temporal modulation of IL-10 activity. In light of these opportunities and challenges, this review aims to provide a comprehensive overview of current IL-10 delivery systems and to highlight strategies for their optimization to facilitate clinical translation in pulmonary diseases.